Urban Transport in Chennai and Bangalore - Mitric, Slobodan; Chatterton, Isabel (World Bank, Washington, DC, 2018)
This report is intended to facilitate the discussions between the World Bank and the Governments of Tamil Nadu and Karnataka, City Governments of Chennai and Bangalore, on possibly expanding the Bank's urban transport assistance in these two cities, and elsewhere in the two states. The report consists of a diagnostic chapter, a discussion of pivotal issues, a reformulated strategy, and a menu of possible Bank-funded projects to support this strategy. Case studies of urban transport in Chennai and Bangalore, the basis for the report, are attached.